WOOD ANATOMY OF Blepharocalyx salicifolius (H.B.K.) Berg - Denardi, Luciano (2005)
The purpose of this work is the description of the wood anatomy of Blepharocalyx salicifolius (H.B.K.) Berg (Myrtaceae). There were collected 6 samples of wood, three from Serra do Sudeste and the others from Campos de Cima da Serra - RS. The wood microtechnique followed the standard procedures used in the Wood Anatomy Laboratory of the Federal University of Paraná. For the maceration of wood sticks, the Jeffrey method was used. The wood anatomy agrees, in general lines, with the typical standard of this family, congregating a large number of narrow and solitary vessels, with simple perforation plates, besides diffuse apotracheal parenchyma, heterogeneous rays and bordered pit fibres. The presence of rhomboid chrystals and the absence of vasicentric tracheids permit to discriminate the studied species from other previously described myrtacean woods, that are native of the State of Rio Grande do Sul.